Postoperative Functional Management Contributes to Anal Functional Recovery in Patients With Low Rectal Cancer After Robotic Total Intersphincteric Resection - Xiaosong, Wang; Hongchang, Liu; Min, Deng; Lijuan, Xie; Chuan, Li; Peiwu, Yu; Bo, Tang (Frontiers in Oncology, 2020)
Purpose: To evaluate the effectiveness of the comprehensive postoperative management including low-frequency endo-anal electrical stimulation and daily suppository usage on postoperative anal functional recovery for low rectal cancer patients who underwent robotic total intersphincteric resection (ISR). Methods: A retrospective analysis was performed on 42 low rectal cancer patients who underwent robotic total ISR, of which 23 patients received comprehensive postoperative management, including biofeedback low-frequency endo-anal electrical stimulation and daily suppository usage (management group). Wexner score and anorectal manometric values, including resting pressure (RP), maximum squeeze pressure (MSP), initial perceived volume (IPV) and maximum tolerated volume (MTV), were assessed and compared. Results: A total of 42 low rectal cancer patients were included in our study. The RP at 6 months after ISR (40.95±6.95 vs 33.29±5.40 mmHg, p=0.002) and MSP at 3 and 6 months after ISR (72.05±10.16 vs 69.05±8.67 mmHg, p=0.031; 91.57±15.47 vs 84.05±12.94 mmHg, p=0.039, respectively) were significantly higher in the management group. The median IPV at 1 and 3 months after ISR (17.81±3.61 vs 15.43±5.08 ml, p=0.038; 20.19±4.35 vs 17.67±5.16 ml, p=0.044, respectively) and MTV at 3 months after ISR (83.71±5.44 vs 76.10±8.42 ml, p=0.012) were significantly higher in the management group. Wexner scores at 1 and 3 months after closure of stoma (COS) in the management group were significantly lower (11.3±2.9 vs 13.4±3.0, p=0.041; 8.9±2.0 vs 10.6±2.4, p=0.036, respectively). Conclusions: Comprehensive postoperative management could accelerate the recovery of sphincteric function and anal sensitivity after robotic total ISR and could also contribute to treatment of fecal incontinence followed by COS.